(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Acinetobacter species are typical nosocomial pathogens causinginfections and high mortality, almost exclusively in compromised hospitalizedpatients. Multidrug-resistant Acinetobacter spp. blood infection in the neonatalintensive care unit patients create a great problem in hospital settings. The studywas done to detect prevalence of acinetobacter spp. as the causative agent ofneonatal sepsis with its antibiogram Materials and methods: A total of 100 clinically suspected neonatal sepsis caseswas enrolled in the study. Bacteriological profile and antibiotic sensitivity pattern ofacinetobacter spp. were done accordingly. Results: Among the 100 suspected neonatal sepsis cases, 28% were culture positiveand 72% were culture negative. Klebsiella species was the predominant isolatedbacteria which was 53.58% followed by Acinetobacter spp. (14.28%) E. coli(10.72%)Pseudomonas spp. (7.14%) S. aureus (7.14%) & Candida (7.14%). Acinetobacter spp.showed 100% resistant to ampicillin, ciprofloxacin, gentamycin, amikacin,ceftazidime, cefotaxime & cefepime, 75% resistant to meropenem & 50% sensitiveto levofloxacin. Conclusion: It is essential to conduct periodic bacteriological profile along withroutine antimicrobial sensitivity testing time to time for effective management ofneonatal sepsis. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 20-23